miR-22 and miR-205 Drive Tumor Aggressiveness of Mucoepidermoid Carcinomas of Salivary Glands - Naakka, Erika; Barros-Filho, Mateus Camargo; Adnan-Awad, Shady; Al-Samadi, Ahmed; Marchi, Fábio Albuquerque; Kuasne, Hellen; Korelin, Katja; Suleymanova, Ilida; Brown, Amy Louise; Scapulatempo-Neto, Cristovam; Lourenço, Silvia Vanessa; Castilho, Rogério Moraes; et al. (Frontiers in Oncology, 2022)
Objectives: To integrate mRNA and miRNA expression profiles of mucoepidermoid carcinomas (MECs) and normal salivary gland (NSGs) tissue samples and identify potential drivers. Material and Methods: Gene and miRNA expression arrays were performed in 35 MECs and six NSGs. Results: We found 46 differentially expressed (DE) miRNAs and 3,162 DE mRNAs. Supervised hierarchical clustering analysis of the DE transcripts revealed two clusters in both miRNA and mRNA profiles, which distinguished MEC from NSG samples. The integrative miRNA-mRNA analysis revealed a network comprising 696 negatively correlated interactions (44 miRNAs and 444 mRNAs) involving cell signaling, cell cycle, and cancer-related pathways. Increased expression levels of miR-205-5p and miR-224-5p and decreased expression levels of miR-139-3p, miR-145-3p, miR-148a-3p, miR-186-5p, miR-338-3p, miR-363-3p, and miR-4324 were significantly related to worse overall survival in MEC patients. Two overexpressed miRNAs in MEC (miR-22 and miR-205) were selected for inhibition by the CRISPR-Cas9 method. Cell viability, migration, and invasion assays were performed using an intermediate grade MEC cell line. Knockout of miR-205 reduced cell viability and enhanced ZEB2 expression, while miR-22 knockout reduced cell migration and invasion and enhanced ESR1 expression. Our results indicate a distinct transcriptomic profile of MEC compared to NSG, and the integrative analysis highlighted miRNA-mRNA interactions involving cancer-related pathways, including PTEN and PI3K/AKT. Conclusion: The in vitro functional studies revealed that miR-22 and miR-205 deficiencies reduced the viability, migration, and invasion of the MEC cells suggesting they are potential oncogenic drivers in MEC.